Douglas County Youth Impact Challenges Evaluation Report - Spohn, Ryan E. (2016)
Douglas County Youth Impact! is a practice model designed to prevent “crossover” youth from moving further into the child welfare or juvenile justice systems. The target population for this initiative is youth that meet the following criteria: 1) the youth must have been referred to the County Attorney’s office for: a) a status offense, or b) a law violation; and 2) the youth has a child welfare case which is: a) open, b) closed within the last 12 months, c) voluntary, or d) court-involved